El Albense superior y el Cenomanense con Foraminíferos bentónicos del sur de la Cordillera Ibérica (provincias de Cuenca y de Valencia) - Fourcade, E.; García de Cortázar, A.; García de Domingo, A.; García Quintana, Álvaro (Cuadernos de Geología Ibérica, 1982)
The age of the first marine deposits of the Upper Cretaceous in the Valencia-Cuenca-Teruel Region is determined by means of benthonic foraminifera distribution. The succesive transgressive episodes are dated as Upper Albian> Upper Albian-Vraconian-Lower Cenomanian and Middle-Upper Cenomaman.